Impact of Public Spending on Private Investment in Malaysia: Crowding-In or Crowding-Out Effect - Sim, Jou Sie; Jerome, Kueh; Muhammad Asraf, Abdullah; Abang Azlan, Mohamad (Universal Publishers - Boca Raton, Florida, USA, 2021)
This study intends to explore the crowding effect of disaggregated public expenditure on private investment in Malaysia from 1980 to 2016 via Vector Error Correction model. Empirical findings show that public spending has an enormous impact on long-term but marginal effect on short-term private investment. Specifically, private investment is significantly crowd-in education and defense of government expenditures while significantly crowd-out health and transportation expenditure in the long term. Nevertheless, there is insufficient evidence on short-run causality between public spending on private investment.